The Impact of Financial Market Instability on Economic Growth and Long-Term Investment - Yulfajar, Amrina; Noor, Gusti Muchran; Putranto, Rachmad Sukma (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study explores the impact of financial market instability on economic growth and long-term investment. It investigates how market volatility, liquidity crises, and weak institutional frameworks influence resource allocation, investor confidence, and sustainable investment sectors, particularly in developing economies. Research Design and Methodology: The research employs a qualitative systematic literature review (SLR) approach, synthesizing theoretical and empirical studies from credible sources such as Emerald, Springer, Elsevier, and Wiley. The SLR method allows for a comprehensive literature analysis to identify trends, gaps, and critical insights regarding financial instability and its broader implications. Findings and Discussion: The findings reveal that financial market instability disrupts capital allocation, weakens investor confidence, and significantly impacts sectors requiring stability, such as green equity markets and infrastructure. Institutional weaknesses exacerbate these effects, particularly in developing countries. Robust regulatory frameworks like Basel III are critical in mitigating instability, enhancing market resilience, and promoting long-term investments. However, the study identifies challenges in regulatory implementation and institutional capacity, emphasizing the need for targeted policy reforms and proactive risk management strategies. Implications: This research underscores the importance of strengthening institutional and regulatory frameworks to stabilize financial markets and foster sustainable economic growth. For practitioners, adopting risk management tools such as portfolio diversification and hedging is essential to protect investments from market volatility. Policymakers are encouraged to develop transparent and inclusive policies that enhance investor confidence and support sustainable investments in critical sectors.